2017
DOI: 10.1103/physreva.96.042707
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic losses in radio-frequency-dressed traps for ultracold atoms

Abstract: (2017) 'Inelastic losses in radio-frequency-dressed traps for ultracold atoms. ', Physical review A., 96 (4). 042707.Further information on publisher's website:https://doi.org/10.1103/PhysRevA.96.042707Publisher's copyright statement:Reprinted with permission from the American Physical Society: Owens, Daniel J. Hutson, Jeremy M. (2017). Inelastic losses in radio-frequency-dressed traps for ultracold atoms. Physical Review A 96(4): 042707 c 2017 by the American Physical Society. Readers may view, browse, and/o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…We also consider 40 Ca 19 F( 2 Σ + ) molecules in this work. In this case, the 19 F nucleus and the electrons contribute 1/2 spin, while 40 Ca has zero nuclear spin. The couplings involving the electron spin have a similar form as discussed above for the hyperfine interactions of 1 Σ molecules, but the coupling constants are typically much larger, as can be seen in Table I.…”
Section: Scattering Calculations a Monomer Hamiltonianmentioning
confidence: 98%
“…We also consider 40 Ca 19 F( 2 Σ + ) molecules in this work. In this case, the 19 F nucleus and the electrons contribute 1/2 spin, while 40 Ca has zero nuclear spin. The couplings involving the electron spin have a similar form as discussed above for the hyperfine interactions of 1 Σ molecules, but the coupling constants are typically much larger, as can be seen in Table I.…”
Section: Scattering Calculations a Monomer Hamiltonianmentioning
confidence: 98%
“…The species-selective manipulations we have demonstrated are only of practical use if the mixture does not suffer large inelastic losses. Recent work concerning a mixture of 85 Rb and 87 Rb indicates that most RF-dressed mixtures are expected to undergo fast inelastic loss [38]; the atom-photon coupling allows inelastic collisions to conserve angular momentum through absorption or emission of an RF photon, allowing spin exchange to occur with large rate coefficients [38,41]. Fortunately, for collisions of 87 Rb atoms, the rate coefficients for spin exchange are small, and it proceeds slowly even for cases that are allowed by angular momentum conservation rules.…”
Section: Collisional Stability Of the Rf-dressed Mixturementioning
confidence: 99%
“…Exploiting this feature, we implement a species-selective double well using MRF-dressed potentials and manipulate the spatial distribution of the individual mixture constituents. Recent theoretical [41] and experimental [38] studies have shown that not all mixtures are collisionally stable when confined in RF-dressed potentials. In this work, we demonstrate the merit of an RF-dressed mixture of 87 Rb F = 1 and F = 2, which we find to be long-lived.…”
Section: Introductionmentioning
confidence: 99%
“…For the colliding pair of molecules we introduce an angular momentum state, |LM L , that describes the end-overend rotation of the intermolecular axis. The basis functions for the pair of molecules are [25][26][27]…”
Section: Theorymentioning
confidence: 99%